Perancangan Aplikasi Student Record dan Practical Project Record Pada AMTO 147 Politeknik Penerbangan Indonesia Curug - Bhima Shakti Arrafat; Wahyu Cakra Nugraha (Jurnal Serambi Engineering, 2025)
The aim of this study is to design a digitally based Student Record and Practical Project Record application that complies with CASR Part 147 and EASA Part 147 standards. This application is expected to overcome various weaknesses of the manual system in recording learning hours, practicals and assessment, such as the risk of document damage, low efficiency and limited data accuracy. The research methodology adopts a systematic approach based on VDI 2222, which includes five main stages: needs analysis, system conceptualisation, technical design, prototype implementation and evaluation of results. The application was implemented using the Laravel framework, cloud-based technology and a responsively designed user interface to ensure data security, ease of access and operational efficiency. Application testing involved the main users, namely learners, teachers and administrators, to evaluate the functionality and performance of the system. The results show that the application is able to record learning and practical hours in accordance with the regulations (3,000 hours for CASR and 2,400 hours for EASA), provide comprehensive assessment reports and facilitate efficient management of practical documents. Therefore, this application has proven to be effective in supporting the management of vocational aviation training and has the potential to become a model for the development of similar systems in other educational institutions. For wider implementation, user training and system optimisation are required to ensure sustainability and adaptability.